Molecular dynamics simulation of the surface wettability of typical minerals in shale. Issue 5 (27th February 2023) - Chen, Junqing; Shi, Kanyuan; Jiang, Fujie; Yang, Xiaobin; Wang, Yuying; Li, Bingyao
Abstract : Nanoscale pores are an important storage space in shale petroleum reservoirs. Mineral surface wettability significantly affects the adsorption ability of a fluid, and it is of great significance for the efficient development of shale petroleum. Within a nanoscale pore, however, we cannot measure the contact angle through a conventional measuring method, so we used a molecular dynamics (MD) simulation method. A nanoscale 'oil–water–rock' wettability model was used to study the wettability of reservoir minerals with micropores. In this study, by means of MD simulation, the wettability models of different minerals (calcite, quartz and illite) and different liquid hydrocarbons ( n ‐hexane, toluene and acetic acid) were established, and then the temperature and pressure were changed to study the influence of mineral type, liquid hydrocarbon type, temperature and pressure on wettability. The results show that calcite has the strongest wettability of water in n ‐hexane, followed by illite and quartz, and toluene has the strongest wettability of water on the surface of calcite minerals, followed by n ‐hexane and acetic acid. In the temperature range of 313–378 K, the higher the temperature, the stronger the water wettability. In the pressure range of 5–20 MPa, the higher the pressure, the water wettability is stronger. By comparing the MD simulation results with the previous experimental results, similar wetting characteristics were obtained, which verified the reliability of the simulation results. This MD simulation method provides a new idea for the study of shale mineral wettability, which is of great significance for shale petroleum exploration. Abstract : Simulation screenshots of the oil and water movement on the mineral surface: (a) calcite; (b) quartz; (c) illite.